Perancangan UI/UX Landing Page Perusahaan Property99 Menggunakan Metode Design Thinking - Evy Nurmiati; Muhamad Miftahul Husna; Musthafa Kamil (Jurnal Manajemen Informatika & Teknologi, 2025)
This study aims to redesign the appearance of the Property99 company landing page with a user-based approach using the Design Thinking method. Property99 as a digital company in the field of building contractor and construction services faces challenges in creating an optimal user experience through the existing landing page. The main problems identified include unresponsive design, confusing navigation, and features that do not support user needs. Through the five stages of Design Thinking: Empathize, Define, Ideate, Prototype, and Test, this study successfully designed a UI/UX Landing Page prototype that is more user-friendly, aesthetic, and functional. The tool used in the design was Figma, while testing was carried out using the Black Box Testing method. The results of the study indicate that this approach is able to improve navigation comfort, user trust, and the effectiveness of the company's information delivery. This research also makes a positive contribution to digital branding and user engagement in the context of the property business.